2004
DOI: 10.1002/jso.20055
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of von Willebrand factor, CD34, CD31, and vascular endothelial growth factor expression in women with uterine leiomyosarcomas

Abstract: Uterine smooth muscle tumors exhibit a lower MVD than normal myometrium, as assessed using anti-FvW or anti-CD34 antibodies. A reduced MVD, as assessed by FvW staining, has prognostic value in uterine LMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…Previous research reported that COL4A2 was overexpressed in fibroid, and that it displayed an anti-angiogenic gene expression profile in fibroids when compared with adjacent normal myometrium. These observations may explain the reduced microvascular density observed in fibroids relative to the myometrium (45) and was in accordance with the reduced microvessel density based on anti-von Willebrand factor immunostaining that was observed in fibroid with respect to normal myometrium (46). Additionally, Gilden et al (47) suggested that protein expression of COL4A2 , versican and fibromodulin was increased in untreated leiomyoma cells compared with untreated patient-matched myometrial cells.…”
Section: Discussionsupporting
confidence: 84%
“…Previous research reported that COL4A2 was overexpressed in fibroid, and that it displayed an anti-angiogenic gene expression profile in fibroids when compared with adjacent normal myometrium. These observations may explain the reduced microvascular density observed in fibroids relative to the myometrium (45) and was in accordance with the reduced microvessel density based on anti-von Willebrand factor immunostaining that was observed in fibroid with respect to normal myometrium (46). Additionally, Gilden et al (47) suggested that protein expression of COL4A2 , versican and fibromodulin was increased in untreated leiomyoma cells compared with untreated patient-matched myometrial cells.…”
Section: Discussionsupporting
confidence: 84%
“…MVD, as an indicator of neovascularization, has been reported to be associated with invasiveness and a high grade of malignancy in many types of cancer such as breast cancer, prostatic cancer and laryngeal cancer [23][24][25]. In the case of LMS, the relationship between MVD and outcome has been controversial, and previous studies have mostly involved LMS arising from the uterus [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…During physiologic angiogenesis, it is produced by a variety of cells, including neutrophils, platelets and macrophages, but its expression is increased in a variety of tumors [21]. In certain tumors, such as in head and neck, breast, gastric, colorectal, cervical and ovarian CA, elevated levels of VEGF correlates not only with increased microvascular density (MVD) but also with poorer prognosis [7,[34][35][36][37][38]. Its role in tumorigenesis has been extensively studied and reviewed [39].…”
Section: Vegfmentioning
confidence: 99%